Genomic and metabolic characterization of a chromophobe renal cell carcinoma cell line model (UOK276). Issue 10 (24th July 2017) - Yang, Youfeng; Vocke, Cathy D.; Ricketts, Christopher J.; Wei, Darmood; Padilla‐Nash, Hesed M.; Lang, Martin; Sourbier, Carole; Killian, J. Keith; Boyle, Shawna L.; Worrell, Robert; Meltzer, Paul S.; Ried, Thomas; et al.
Abstract: Chromophobe renal cell carcinoma (ChRCC) represents 5% of all RCC cases and frequently demonstrates multiple chromosomal losses and an indolent pattern of local growth, but can demonstrate aggressive features and resistance to treatment in a metastatic setting. Cell line models are an important tool for the investigation of tumor biology and therapeutic drug efficacy. Currently, there are few ChRCC‐derived cell lines and none is well characterized. This study characterizes a novel ChRCC‐derived cell line model, UOK276. A large ChRCC tumor with regions of sarcomatoid differentiation was used to establish a spontaneously immortal cell line, UOK276. UOK276 was evaluated for chromosomal, mutational, and metabolic aberrations. The UOK276 cell line is hyperdiploid with a modal number of 49 chromosomes per cell, and evidence of copy‐neutral loss of heterozygosity, as opposed to the classic pattern of ChRCC chromosomal losses. UOK276 demonstrated a TP53 missense mutation, expressed mutant TP53 protein, and responded to treatment with a small‐molecule therapeutic agent, NSC319726, designed to reactivate mutated TP53. Xenograft tumors grew in nude mice and provide an in vivo animal model for the investigation of potential therapeutic regimes. The xenograft pathology and genetic analysis suggested that UOK276 was derived from the sarcomatoid region of the original tumor. In summary, UOK276 represents a novel in vitro and in vivo cell line model for aggressive, sarcomatoid‐differentiated, TP53 mutant ChRCC. This preclinical model system could be used to investigate the novel biology of aggressive, sarcomatoid ChRCC and evaluate the new therapeutic regimes.